1997
DOI: 10.1046/j.1365-2036.1997.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy of bismuth carbomer enemas in patients with treatment‐resistant chronic pouchitis

Abstract: Background: Mucosal inflammation of the ileal pouch (pouchitis) is the major long‐term complication after ileal pouch‐anal anastomosis for ulcerative colitis. Broad‐spectrum antibiotics are the mainstay of treatment, however, 15% of patients with pouchitis have a chronic, treatment‐resistant disease. Aim: To determine the safety and efficacy of bismuth carbomer enemas in achieving and maintaining remission in treatment‐resistant chronic pouchitis. Methods: Twelve patients with treatment‐resistant chronic pou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…In a study of colitis in the rat, this group also showed that both BSS and CBS had efficacy in healing colitis (10). This result concurs with results from several recent clinical reports demonstrating efficacy of oral BSS in microscopic colitis (11) and bismuth carbomer enemas in treatment-resistant chronic pouchitis (12).…”
supporting
confidence: 82%
“…In a study of colitis in the rat, this group also showed that both BSS and CBS had efficacy in healing colitis (10). This result concurs with results from several recent clinical reports demonstrating efficacy of oral BSS in microscopic colitis (11) and bismuth carbomer enemas in treatment-resistant chronic pouchitis (12).…”
supporting
confidence: 82%
“…In an open label trial lasting 45 days, bismuth carbomer enemas appeared effective for chronic treatment-resistant pouchitis. 12 Perhaps a longer treatment period in this current study would have shown a therapeutic bene®t. 12 (8±17) 9 (2±16)à 11 (7±16) 9 (2±16)à * Two subjects missing data at completion in bismuth group.…”
Section: Discussionmentioning
confidence: 99%
“…9±11 More recently, bismuth complexed with carbomer (an acrylic acid polymer) and administered as a liquid enema was reported to result in clinical improvement in 10 of 12 patients in an open trial. 12 The rationale for the use of bismuth and bismuth carbomer in ulcerative colitis and pouchitis includes both non-speci®c anti-diarrhoeal effects and anti-bacterial effects. Some preparations of bismuth no longer in use caused neurotoxicity when taken in high doses, such as bismuth subnitrate in France and bismuth subgallate in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…These modalities include budesonide [36], bismuth carbomer enema [37], glutamine and butyrate suppository compounds [38], and allopurinol [39]. None of these therapies have shown significant beneficial effect in comparison to placebo [17].…”
Section: Do Antibiotics Improve Pouchitis Symptoms?mentioning
confidence: 99%